2015
DOI: 10.3109/02699206.2015.1056884
|View full text |Cite
|
Sign up to set email alerts
|

Covert contrast in velar fronting: An acoustic and ultrasound study

Abstract: There is growing evidence that speech sound acquisition is a gradual process, with instrumental measures frequently revealing covert contrast in errors perceived to involve phonemic substitution. Ultrasound imaging has the potential to expand our understanding of covert contrast by showing whether a child uses different tongue shapes while producing sounds that are perceived as neutralized. This study used an ultrasound measure (Dorsum Excursion Index) and acoustic measures (VOT and spectral moments of the bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 33 publications
(49 reference statements)
1
25
0
3
Order By: Relevance
“…Ultrasound tongue imaging (UTI) is a relatively new tool to clinical phonetics, with as far as we are aware only one recent study using it to identify covert contrast (McAllister-Byun, Buchwald & Mizoguchi, 2015) and a different study by Bressmann, Radovanovic, Kulkarni, Klaiman, and Fisher (2011) using the technique to show covert articulatory movements in speakers with cleft palate. UTI uses standard medical ultrasound to image the tongue in real-time making it suitable for visual biofeedback therapy, with over 20 small studies showing it to be effective for treating persistent speech sound disorders (see for example, Cleland, Scobbie & Wrench, 2015) and other studies using it for fine articulatory analysis of lingual movements when synchronised to the acoustic signal (for example, Heyde, Scobbie, Lickley, and Drake, 2015).…”
Section: Ultrasound Tongue Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound tongue imaging (UTI) is a relatively new tool to clinical phonetics, with as far as we are aware only one recent study using it to identify covert contrast (McAllister-Byun, Buchwald & Mizoguchi, 2015) and a different study by Bressmann, Radovanovic, Kulkarni, Klaiman, and Fisher (2011) using the technique to show covert articulatory movements in speakers with cleft palate. UTI uses standard medical ultrasound to image the tongue in real-time making it suitable for visual biofeedback therapy, with over 20 small studies showing it to be effective for treating persistent speech sound disorders (see for example, Cleland, Scobbie & Wrench, 2015) and other studies using it for fine articulatory analysis of lingual movements when synchronised to the acoustic signal (for example, Heyde, Scobbie, Lickley, and Drake, 2015).…”
Section: Ultrasound Tongue Imagingmentioning
confidence: 99%
“…In both views, the imageable area is constrained by shadows from bone, with the tongue tip in particular being susceptible to a shadow from the mandible. Unlike EPG, the speaker is not required to have any custom-made appliances and as such it is potentially a quicker and easier way to identify covert contrast (McAllister Byun et al, 2015) which might translate to the clinic if simple analysis methods can be found. The purpose this this study was therefore to contribute one such analysis method so that ultrasound can be used for diagnosis of specific types of speech disorders (Bressmann et al, 2011) and remediation of the same errors .…”
Section: Ultrasound Tongue Imagingmentioning
confidence: 99%
“…However, it is possible that, for specific distinctions, as the contrast of the articulatory point, the difference has been marked in a not measured parameter. The use of the covert contrast was observed in the English data (29) , in the speech of only one child with velar anteriorization, by acoustic and ultrasound measures.…”
Section: Discussionmentioning
confidence: 99%
“…However, instead of affirming the existence of this kind of contrast, it was chosen to assume the idea that the proportions of the significant axes cannot be sensible to the detection of covert contrasts. This way, it was possible infer a superiority of the acoustical analysis in the understanding of data covert gestures and analysis here considered, consenting with the findings of another study (29) . However, it is possible that, for specific distinctions, as the contrast of the articulatory point, the difference has been marked in a not measured parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound imaging may also be useful diagnostically, e.g., to characterize errors in lingual shapes, 26,27 , or to identify sub-perceptible or covert contrasts in disordered speech 28,29 . If precise articulatory measurements are being obtained and compared, it is essential that the ultrasound be stabilized so that the coordinate space for measurement remains reasonably constant.…”
Section: Introductionmentioning
confidence: 99%